Emotional-symbolic communication as a predictor of communicative competence in professional subculture - Lebedeva, Liudmila D.; Timofeeva, Tatiana I. (Social Welfare: Interdisciplinary Approach, 2011)
The article gives a short outline of different approaches to studying the problem of emotional symbolic communication. Some theoretical results of the research into this phenomenon as a predictor of building up communicative competence of those doing socialnomics jobs have been discussed. The role of constant communicative patterns in self-identification of young people and development of professional subculture is presented.